A non-coding region near Follistatin controls head colour polymorphism in the Gouldian finch. Issue 1888 (10th October 2018) - Toomey, Matthew B.; Marques, Cristiana I.; Andrade, Pedro; Araújo, Pedro M.; Sabatino, Stephen; Gazda, Małgorzata A.; Afonso, Sandra; Lopes, Ricardo J.; Corbo, Joseph C.; Carneiro, Miguel
Abstract : Discrete colour morphs coexisting within a single population are common in nature. In a broad range of organisms, sympatric colour morphs often display major differences in other traits, including morphology, physiology or behaviour. Despite the repeated occurrence of this phenomenon, our understanding of the genetics that underlie multi-trait differences and the factors that promote the long-term maintenance of phenotypic variability within a freely interbreeding population are incomplete. Here, we investigated the genetic basis of red and black head colour in the Gouldian finch ( Erythrura gouldiae ), a classic polymorphic system in which naturally occurring colour morphs also display differences in aggressivity and reproductive success. We show that the candidate locus is a small (approx. 70 kb) non-coding region mapping to the Z chromosome near the Follistatin ( FST ) gene. Unlike recent findings in other systems where phenotypic morphs are explained by large inversions containing hundreds of genes (so-called supergenes), we did not identify any structural rearrangements between the two haplotypes using linked-read sequencing technology. Nucleotide divergence between the red and black alleles was high when compared to the remainder of the Z chromosome, consistent with their maintenance as balanced polymorphisms over several million years. Our results illustrate how pleiotropic phenotypes can arise from simple genetic variation, probably regulatory in nature.